Application for Searching for Livestock Distributor Locations at the North Sumatra Plantation and Livestock Service Using the Euclidean Distance Method - Aulia, Prayogi; Syahrin, Elvin (Marqcha Institute, 2025)
The Plantation and Livestock Agency of North Sumatra Province plays an important role in supporting the availability and distribution of livestock for farmers and livestock business actors. However, information about the locations of livestock distributors, which are scattered across various regions, is often difficult to access quickly and accurately. This situation makes the process of finding distributor locations inefficient and time-consuming. Therefore, a system is needed to help users find the nearest livestock distributor locations automatically and accurately. This study aims to design and develop an Android-based application that provides information on livestock distributor locations in North Sumatra Province and determines the nearest distance between the user and the distributors using the Euclidean Distance method. This method is used to calculate the distance between two points based on their geographic coordinates (latitude and longitude), allowing users to get recommendations for the nearest distributor from their current position. The result of this study is an Android application that can display a list of livestock distributors, show their locations on a map using GPS services, and provide real-time information about the closest distance. This application is expected to make the process of finding livestock distributor locations more effective and efficient, as well as help the Plantation and Livestock Agency of North Sumatra Province provide digital information services to the public.